The Mitford Vanishing - Book 5 - Fellowes, Jessica (Thorndike, Maine : Center Point Large Print, 2022)
"1937. War with Germany is dawning, and a civil war already rages in Spain. Split across political lines, the six Mitford sisters are more divided than ever. Meanwhile their former maid, Louisa Cannon Sullivan, is now a private detective, working with her ex-policeman husband Guy Sullivan. Louisa and Guy are surprised when a call comes in from novelist Nancy Mitford requesting that they look into the disappearance of her Communist sister Jessica in France. But one case leads to another as they are also asked to investigate the mysterious vanishing of another woman. As the two cases come together, Louisa and Guy discover that every marriage has its secrets - but some are more deadly than others. Suddenly home feels a long way away."--
Keywords: Mitford, Jessica, -- 1917-1996 -- Fiction; Missing persons -- Investigation; Fiction; Sisters -- Fiction; Women private investigators -- England; Fiction; Great Britain -- History -- 20th century; Fiction; Detective and mystery fiction; Historical fiction